Pediatric Ocular Myasthenia Gravis: A Review - Jain, Reena; Aulakh, Roosy (Journal of Pediatric Neurology, 2020)
Pediatric ocular myasthenia gravis (OMG) is difficult to diagnose and manage, owing to its rarity and low index of suspicion in the early stage of the disease. Also, many other conditions having similar presentation cause a further delay in diagnosis. In this review, we highlighted various pointers in history and described bedside clinical tests that can aid in its timely diagnosis. The antibody spectrum in myasthenia is ever increasing and includes anti-muscle specific kinase and low-density lipoprotein-receptor related protein 4 antibodies in addition to acetylcholine receptor antibodies besides many others. However, pediatric OMG patients often test negative for all three antibodies, making the diagnosis even more difficult in triple seronegative patients. Edrophonium and electrophysiological tests, which help in confirming myasthenia in adults, have a limited utility in diagnosing pediatric ocular myasthenia cases. Various practical difficulties are encountered like nonavailability of edrophonium, risk of bradycardia associated with neostigmine use and its lower sensitivity, noncooperative children, and limited technical expertise in performing electrophysiological tests in children. In this article, we described a pragmatic approach to diagnose pediatric OMG along with the important aspects of its management.
Keywords: juvenile ocular myasthenia; ptosis; diplopia; immunosuppressant drugs